Performance Evolution of Recycled Aggregate Concrete under the Coupled Effect of Freeze–Thaw Cycles and Sulfate Attack - Pu Jia; Lang Li; Jin Zhou; Di Zhang; Zhongwei Guan; Jiangfeng Dong; Qingyuan Wang (Applied Sciences, 2022)
The high porosity of recycled coarse aggregate, which results in recycled aggregate concrete (RAC) more vulnerable to freeze–thaw (FT) damage and chemical attack, is a dominant factor that limits the industrialization of recycled aggregate concrete in civil engineering. This paper presents an experimental study on the combined effects of FT damage and sulfate attack on mechanical properties of high-performance RAC. The influence of the combined damage on the mass, solution-filled pore volume, dynamic elastic modulus, compressive strength, splitting tensile strength and fracture energy of RAC was studied. Results showed that the water-exposed FT cycles would result in more severe deterioration in the mass loss, elastic modulus and compressive strength, while for the sulfate-exposed FT cycles, the splitting tensile strength and fracture energy have more significant degradation. Moreover, compared with compressive strength, deterioration in splitting tensile strength is more severe. The maximum losses in compressive and splitting tensile strength were 28.7% and 35%, respectively. The fracture energy showed an increasing trend to 60 FT cycles, followed by an overall decrease to 180 FT cycles. The fracture energy exhibits a maximum increment of about 45% and 39% for water- and sulfate-exposed samples, respectively, after being subjected to 60 FT cycles. The analysis of failure modes of coarse aggregate has revealed that FT damage results in a significant deterioration in the binding force of mortar. After being subjected to 180 FT cycles, the area percentage of pulled-out failure was increased from 7.3% to larger than 17.3%.